EMPLOYMENT FROM A GENDER PERSPECTIVE IN BALI PROVINCE - Ida Ayu Gde Dyastari Saskara; Anak Agung Istri Ngurah, Marhaeni (Universitas Mataram, 2024)
Opportunities for women and men to compete in the job market are needed to accelerate increases in community productivity. Decent employment opportunities can be seen through the unemployment approach and the level of inactivity from non-labor force indicators. Inequality in development according to gender can result in suboptimal potential obtained from development. There is still visible discrimination or inequality towards female workers and male workers that can be seen from the contribution of women's income, the number of working hours, women's participation in labor force and the involvement of women in positions in professional. This is due to the existence of stereotypes about gender, apart from that, women are also faced with their natural instincts as women in taking care of the family, which results in the contribution of women's workforce not being optimal even though their human capital is equivalent to that of men's workers